A unique, inexpensive, and abundantly available adsorbent: composite of synthesized silver nanoparticles (AgNPs) and banana leaves powder (BLP). Issue 4 (April 2022) - Darweesh, Mona A.; Elgendy, Mahmoud Y.; Ayad, Mohamed I.; Ahmed, Abdel Monem M.; Kamel Elsayed, N.M.; Hammad, W.A.
Abstract: The purpose of this study is to investigate the development of a new and inexpensive adsorbent by immobilization synthesized silver nanoparticles (AgNPs) onto banana leaves powder (BLP), and the prepared composite (BLP)/(AgNPs) was used as an adsorbent for Zn(II), Pb(II), and Fe(III) ion removal from aqueous solutions under the influence of various reaction conditions. (BLP)/(AgNPs) demonstrated remarkable sensitivity toward Zn (II), Pb (II), and Fe (III) ions; metal ions eliminations increased with increasing contact time, agitation speed, adsorbent dose, and temperature, yielding adequate selectivity and ideal removal efficiency of 79%, 88%, and 91% for Zn (II), Pb (II), and Fe (III) ions, respectively, at pH = 5 for Zn(II) and pH = 6 for Pb(II), and Fe(III). The equilibrium contact time for elimination of Zn (II), Pb (II), and Fe (III) ions was reaches at 40 min. Langmuir, Freundlich, and Temkin equations were used to test the obtained experimental data. Langmuir isotherm model was found to be more accurate in representing the data of Zn(II), Pb(II), and Fe(III) ions adsorption onto (BLP)/(AgNPs), with a regression coefficient (R 2 = 0.999) and maximum adsorption capacities of 190, 244, and 228 mg/g for Zn(II), Pb(II), and Fe(III) ions, respectively. The thermodynamic parameters proved that adsorption of metal ions is spontaneous, feasible, and endothermic, whereas Kinetic studies revealed that the process was best described by a pseudo second order kinetics. Highlights: By reduction reaction, silver nanoparticles were impregnated in banana leaves homogeneous powder and used as an adsorbent. The fabricated composites are used as adsorbent for the removal of Zn (II), Pb (II), and Fe (III) ions from aqueous solutions. The new adsorbent exhibited high adsorption capacity with three metal ions and followed the order Pb (II)> Fe (III) >Zn (II) ions. The metal ions vanished from the solution within approximately 40 min. Abstract : Agriculture waste, Banana leaves, Heavy metals, Ions removal, Silver nanoparticles, Adsorption kinetics, Adsorption isotherm.